First record of Cyclosiella spiralis (Arctiidae) from Peninsular Malaysia - Muhamad Ikhwan, Idris; Fatimah, Abang (Malayan Nature Journal., 2011)
The Arctiidae family of small to medium-sized moths have antennae that are usually bipectinate or ciliate in the males, the pectination or ciliation being reduced or absent in the females (Barlow 1982). The proboscis is reduced and short, and the palpi are also generally short (Barlow 1982). Lithosiinae is the largest subfamily of Arctiidae in the oriental tropics and Bornean lithosiinae include 298 species in 70 genera (Holloway 2001). Records of host-plants for arctiids indicate that a large number of lithosiine larvae are lichen, algal, liverwort or moss browsers. The larvae tend to graze on these wherever they are abundant, such as moist walls, cliffs and rocks, the trunks and branches of trees and, in very humid biotopes, on leaves (Holloway 2001). Most other arctiids tend towards polyphagy with some concentration on weedy herbaceous plant taxa (Barlow 1982, Holloway 1988, Holloway 2001).